Glutamate promotes triple-negative breast cancer development through IRE1α/XBP1-mediated macrophage polarization: mechanism insights and therapy - Hao Wang; Jifeng Sun; Zhansheng Jiang; Zhongsheng Tong; Chen Wang (Discover Oncology)
Abstract Background Triple-negative breast cancer (TNBC) is a highly aggressive malignancy associated with early recurrence, metastatic propensity, and poor clinical outcomes, yet its underlying molecular mechanisms remain incompletely elucidated. This study aims to investigate the role of glutamate in promoting macrophage polarization and TNBC progression via the IRE1α/XBP-1 signaling pathway. Methods The growth and pathological changes of tumor and the protein expression levels of p-PERK, ATF6, IRE1α, XBP-1, G-CSF, GM-CSF, arginase-1, CD206, iNOS and TNF-α in tumor cells were observed in vivo experiments. The expression levels of IL-6, G-CSF and GM-CSF in MCF-7 cells and MDA-MB-231 cells as well as cell proliferation, migration, invasion and cell viability were observed in vitro experiments. Results In the vivo experiments, compared with common breast cancer tumors and TNBC tumors without overexpressing glutaminase 1 (GLS1), the tumor volume of TNBC with overexpressing GLS1 increased significantly, and the tissue necrosis increased (p < 0.05). After GLS1 overexpression, the levels of P-PERK, ATF6, IRE1α, XBP-1, G-CSF, GM-CSF, arginase-1 and CD206 in TNBC tumors significantly increased, while the levels of iNOS and TNF-α significantly decreased (p < 0.05). In the vitro experiments, compared to MCF-7 cells and MDA-MB-231 cells without the XBP-1 inhibitor toyocamycin, the levels of IL-6, G-CSF, GM-CSF, cell proliferation, migration, invasion ability, and cell viability in MDA-MB-231 cells supplemented with the XBP-1 inhibitor toyocamycin were significantly reduced (p < 0.05). Conclusions Glutamate can promote macrophage polarization and the development of TNBC by upregulating IRE1α/XBP-1. Targeted inhibition of glutamate metabolism or IRE1α/XBP-1 pathway can effectively block the proliferation of TNBC tumor cells, providing a basis for the study of targeted drugs to treat TNBC.